Pengaruh Bullying terhadap Motivasi Belajar Peserta Didik di Sekolah Dasar - Syilfa Nirwana (Lembaga Pengembangan Kinerja Dosen, 2024)
Bullying refers to deviant behavior that is often carried out consciously or unconsciously. Bullying is repeated aggressive and negative behavior towards someone with the aim of hurting him. Bullying is defined as negative actions carried out by a stronger party against a weaker party through the use or non-use of tools with the aim of creating physical and emotional pressure on the weaker party. The increase in bullying cases in schools shows how worrying the current condition of education in Indonesia is. The aim of this research is to find out whether bullying behavior has a significant influence on students' learning motivation and enthusiasm for learning. We hope this can help schools know how big the impact of bullying is at school and help victims overcome the problems and risks of bullying. The method used is the Systematic Literature Review or SRL method, namely selecting each journal or previous research and getting results in the form of references for models/ideas that will be developed in the future. The results of this research show that bullying has a big influence on students' learning motivation, this is characterized by not having the courage to participate actively in the learning process and showing low interest in lessons. Bullying behavior significantly affects elementary school students' learning motivation. Students who experience bullying tend to show lower levels of motivation, loss of interest in learning, and lack of confidence in their academic abilities.